Impact of the number of tubes containing nanofluid flow on the melting and freezing of phase change materials in the thermal management of plate lithium-ion batteries. (June 2023) - Chen, Haiji; Zhou, Wanlin; Yuan, Yanjie; Heidarshenas, Behzad
Abstract: Phase change material (PCM) and nanofluids (NFs) flow are used in three-dimensional simulations for the thermal management (TMGT) of a plate battery. On each side of the battery, there are two enclosures in which the PCM is housed. Within the PCM, there is a tube that allows alumina/water NFs to flow. The two-phase model is used to simulate the NFs flow, the number of tubes inside the PCM is varied from 1 to 4, and the NFs velocity (VNF) is changed from 10 to 30 mm/s. Also, the distance of the tubes from the battery center changes to determine the volume fraction of molten PCM (VFMPC) and the maximum temperature of the battery (T-BT). For the simulations, the finite element technique (FEM) is used. The findings show that the lowest maximum T-BT and VFMPC are caused by a 5-mm distance between the tubes, whereas the greatest maximum temperature (T-MX) and VFMPC are caused by an 8-mm gap. The use of more tubes in PCM causes the VFMPC to be decreased. Besides, the maximum T-BT is reduced with time. Enhancing the VNF causes the maximum T-BT to decrease. The maximum T-BT is decreased by 45.37% in 1200 s by adjusting the VNF from 10 to 30 mm/s.